Anatomical inputs to sulcal portions of areas 9m and 8Bm in the macaque monkey - Eradath, Manoj K.; Abe, Hiroshi; Matsumoto, Madoka; Matsumoto, Kenji; Tanaka, Keiji; Ichinohe, Noritaka (Frontiers in Neuroanatomy, 2015)
Neuronal activities recorded from the dorsal bank of the anterior cingulate sulcus have suggested that this cortical area is involved in control of search vs. repetition, goal-based action selection and encoding of prediction error regarding action value. In this study, to explore potential anatomical bases for these neuronal activities, we injected retrograde tracers (CTB-Alexa-488 and CTB-gold) into the dorsal bank of the anterior cingulate sulcus and examined the distribution of labeled cell bodies in macaque monkey brains. The Nissl staining showed that the cortex in the dorsal bank of the anterior cingulate sulcus has consistent layer 4 which means that the cortical region is a part of the granular prefrontal cortex.. The injection site belonged to the sulcal portion of area 9m in two cases and the sulcal portion of area 8Bm in one case. In addition to the continuous distribution of labeled cells in the two areas (areas 9m and 8Bm) around the injection site, the labeled cells were densely distributed in the cingulate areas (areas 24, 32 and 23) in all the cases. The dense labeling of cells was also found in other prefrontal areas (areas 46, 10, 11 and 12) in the two cases with injection into the sulcal portion of area 9m, whereas the dense labeling of cells was found in pre-motor areas (F6 and F7) in the case with injection into the sulcal portion of area 8Bm. The dense labeling of cells in the prefrontal and premotor areas was more similar to those previously found after injections into dorsal parts of areas 9 and 8B. Subcortical distribution of labeled cells was found in the mediodorsal nucleus of thalamus, claustrum and substantia nigra pars compacta in all the cases.